Impact of an Institutional Antimicrobial Stewardship Program on Bacteriology of Surgical Site Infections in Cardiac Surgery. Issue 6 (5th May 2016) - Ashfaq, Adeel; Zhu, Allen; Iyengar, Amit; Wu, Hoover; Humphries, Romney; McKinnell, James A.; Shemin, Richard; Benharash, Peyman
Abstract: Background: Surgical site infections (SSIs) occur in 1% to 4% of cardiac surgery patients and are associated with significantly reduced survival. The present study evaluated trends in the incidence and bacteriology of SSIs before and after the implementation of an antimicrobial stewardship program. Methods: Starting in 2010, our institution utilized a protocol that included daily chlorhexidine baths, and strict cessation of prophylactic antibiotics after 48 hours. We used our institutional Society of Thoracic Surgery Database to identify all adult patients who underwent cardiac operations. Data from the microbiology laboratory were used to identify SSIs. Patients undergoing cardiac surgery between January 2008 and December 2010 (pre‐stewardship group: PRE) and January 2011 and December 2012 (post‐stewardship group: POST) were compared. Results: Of the 3233 patients who underwent cardiac surgery during the study period, 23 (0.71%) developed SSIs (PRE: 0.69%, POST: 0.75%, p   = 0.843). The proportion of gram positive, gram negative, fungal, and anaerobic organisms was not significantly different between time periods. The most commonly identified organisms were Staphylococcus aureus, Enterococcus spp ., and Pseudomonas aeruginosa . Conclusion: Despite changes in antibiotic prophylaxis duration and postoperative skin treatment, our data demonstrate a stable incidence and composition of surgical wound infections during the study period. doi: 10.1111/jocs.12756 (J Card Surg 2016;31:367–372)